Maternal Health and Its Impact on Maternal Morbidity and Mortality - Mashael Mahdi Saleh Alshulah et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Abstract Maternal health is a critical component of public health, impacting not only the lives of mothers but also the well-being of families, communities, and future generations. Maternal morbidity and mortality are significant indicators of healthcare system quality, particularly in low- and middle-income countries, where limited access to healthcare services exacerbates these issues. This review discusses the key factors affecting maternal health, the main causes of maternal morbidity and mortality, and the impact of various interventions aimed at improving maternal health outcomes. Keywords: Maternal Health, Maternal Morbidity, Maternal Mortality. Received Date: September 13, 2024 Accepted Date: October 11, 2024 Published Date: November 09, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/195 DOI: https://doi.org/10.5281/zenodo.14060054